Transformative Nanosized Organic Coatings with Euphorbia Condylocarpa/Poplar Tree Bark/Zircon Silicate Hybrid System for Enhanced Industrial Resilience - Yilmaz, Kubra; Sahin, Fatma Irem; Acarali, Nil (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2024)
This study focused on enhancing the properties of interior coatings by incorporating natural additives to minimize potential health impacts associated with traditional additives. Organic additives such as Euphorbia condylocarpa , poplar tree bark, and zircon silicate were employed by utilizing Design Expert for optimization. The optimized formulation demonstrated impressive attributes including the prevention of bacterial and mold growth, high corrosion resistance, effective coverage and adhesion, and resistance to dirt retention. The recommended optimum formulation, Euphorbia condylocarpa (1%), poplar tree bark (1%), and zircon silicate (1%) by using the 2FI model, exhibited an R 2 value of 0.9838, indicating a remarkable predictability of the variability in the experimental data. This result emphasized the effectiveness of the proposed model in optimizing the properties of nanosized organic coatings for various industrial applications. Thermogravimetric and differential thermal analysis (TG-DTA) revealed that the additives contributed to the development of flame-retardant properties as the temperature increased and morphology of coating was obtained with optical microscope and scanning electron microscope (SEM). Specifically, Euphorbia condylocarpa exhibited antibacterial, flame-retardant, and hydrophobic properties. The study concluded that the incorporation of euphorbia plant, poplar tree bark, and zircon silicate substances positively impacted the performance of coatings offering a more health-conscious and technologically advanced alternative.
Keywords: Euphorbia condylocarpa; zircon silicate; poplar tree bark; interior coating; Engineering